EARNING PER SHARE (EPS), DIVIDENDS PAYOUT RATIO (DPR) AND DEBT TO EQUITY RATIO (DER) AND ITS EFFECT ON COMPANY SHARE PRICE - Friyanto Friyanto; Suyitno Suyitno; Raden Haryo Tirtosetianto; Moehammad Nasri Abdoel Wahid (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Factors affecting the stock price movement are internal factors and external factors. The internal factor related to revenue that will be earned by investors which are dividends or capital gains. The samples were LQ 45 companies that were active in the Indonesia Stock Exchange during the period 2017 – 2019. The total populations were 45 companies and after the process of selecting with purposive sampling method acquired 15 companies. This study used secondary data in the form of a company's financial statement that was published in the Indonesia Stock Exchange on the website www.idx.co.id. Analysis method used multiple regression with partially test (t test) and simultaneously (F test). The study resulted for EPS showing a significant value that was mean there was a partial effect to the stock price of LQ 45 companies. For the result of DPR and DER didn't show significant value that was mean there weren't partial effect of both to stock price of LQ 45 companies. From the simultaneous test (F test) showed the significant value of EPS, DPR and DER, which means there were simultaneous effects to the stock price of LQ 45 companies